Omega‐3 polyunsaturated fatty acid supplementation reduces blood pressure but not renal vasoconstrictor response to orthostatic stress in healthy older adults. Issue 8 (19th April 2018) - Clark, Christine M.; Monahan, Kevin D.; Drew, Rachel C.
Abstract: Older adults exhibit augmented renal vasoconstriction during orthostatic stress compared to young adults. Consumption of omega‐3 polyunsaturated fatty acids, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) found in fish oil (FO), modulates autonomic nerve activity. However, the effect of omega‐3 polyunsaturated fatty acid consumption on the renal vasoconstrictor response to orthostatic stress in young and older adults is unknown. Therefore, 10 young (25 ± 1 years; mean ± SEM) and 10 older (66 ± 2 years) healthy adults ingested 4 g FO daily for 12 weeks, and underwent graded lower body negative pressure (LBNP; −15 and −30 mmHg) pre‐ and post‐FO supplementation. Renal blood flow velocity (RBFV; Doppler ultrasound), arterial blood pressure (BP; photoplethysmographic finger cuff), and heart rate (electrocardiogram) were recorded. Renal vascular resistance (RVR), an index of renal vasoconstriction, was calculated as mean BP/RBFV. All baseline cardiovascular values were similar between groups and visits, except diastolic BP was higher in the older group ( P  <   0.05). FO supplementation increased erythrocyte EPA and DHA content in both groups ( P  <   0.05). FO did not affect RVR or RBFV responses to LBNP in either group, but attenuated the mean BP response to LBNP in the older group (older −30 mmHg: pre‐FO −4 ± 1 vs. post‐FO 0 ± 1 mmHg, P  <   0.05; young −30 mmHg: pre‐FO −5 ± 1 vs. post‐FO −5 ± 2 mmHg). In conclusion, FO supplementation attenuates the mean BP response but does not affect the renal vasoconstrictor response to orthostatic stress in older adults. Abstract : The novel findings of this study are that fish oil supplementation attenuates the mean blood pressure response but does not affect the renal vasoconstrictor response to orthostatic stress in healthy older adults. These findings may have implications for omega‐3 polyunsaturated fatty acid consumption in older adults to reduce orthostatic hypotension.